PEMANFAATAN PROTOKOL TCP/IP UNTUK PROGRAM CHATTING DENGAN VISUAL BASIC - Pipin Farida Ariyani (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2011)
In recent years, computer technology has developed very rapidly. Due to the very rapid development of this technology, then one technology with others should become interlinked. The differences that occur in the collection, transmission, storage and processing of information can be overcome. In this case allows the user to obtain information quickly and accurately. The need for exchange information between those computers requires connection among them. The problem that arises in the delivery of information among them is the lack of computer facilities that support user activities in the delivery of information. From those existing computers, not all of them have a good external drive. Some of them are error or they do not have those facilities in their computer. For example not all computers are connected to the internet, so the users do not freely send files via e-mail. Since there many constrains that exist, the communication should be fast and precise. The chatting program installed is necessary to be built in a small network called Local Area Network (LAN). Information exchange carried out in the form of text, pictures (emotion icons), and sending a file can be selected by the use according to the current needs.Keywords: LAN, chatting, protocol TCP/IP, Visual Basic